Wage and Productivity Effect of Continuing Training in Germany: A Sectoral Analysis - Anja Kuckulenz (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
Wage and productivity effects of training are compared to study how the training rent is shared between employers and employees. With panel data from 1996-2002, I analyse the impact of continuing training on wages and productivity in a Cobb-Douglas production framework. Using system GMM techniques allows me to account for endogeneity and time invariant unobserved factors. Results suggest that the training rent is shared between employer and employee due to a positive effect of continuing training on both wages and productivity. The effect on productivity is about three times higher than the one on wages. High skilled workers capture a larger share of the rent than low skilled workers.
Keywords: C23; C21; J24; J31; 330; continuing vocational training; system GMM estimation; wage effect; productivity effect; external effect; Weiterbildung; Betriebliche Weiterbildung; Bildungsertrag; Rententheorie; Lohn; Produktivität; Externer Effekt; Schätzung; Deutschland